2023
DOI: 10.3390/ijms24087260
|View full text |Cite
|
Sign up to set email alerts
|

The FomYjeF Protein Influences the Sporulation and Virulence of Fusarium oxysporum f. sp. momordicae

Abstract: Fusarium oxysporum causes vascular wilt in more than 100 plant species, resulting in massive economic losses. A deep understanding of the mechanisms of pathogenicity and symptom induction by this fungus is necessary to control crop wilt. The YjeF protein has been proven to function in cellular metabolism damage-repair in Escherichia coli and to play an important role in Edc3 (enhancer of the mRNA decapping 3) function in Candida albicans, but no studies have been reported on related functions in plant pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this study, FoPV1 was shown to have a reduced pathogenicity phenotype according to the comparison of the virulence of the present strain of FoPV1 (FCR51) and the cured strain of the virus (FCR51VF). Moreover, compared with the cured strain (FCR51VF), FCR51 has a lower conidia production, which is a positive correlation with the virulence of F. oxysporum [ 48 ]. Thus, FoPV1 has obvious hypovirulence to F. oxysporum by directly or indirectly reducing sporulation function.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, FoPV1 was shown to have a reduced pathogenicity phenotype according to the comparison of the virulence of the present strain of FoPV1 (FCR51) and the cured strain of the virus (FCR51VF). Moreover, compared with the cured strain (FCR51VF), FCR51 has a lower conidia production, which is a positive correlation with the virulence of F. oxysporum [ 48 ]. Thus, FoPV1 has obvious hypovirulence to F. oxysporum by directly or indirectly reducing sporulation function.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, F. oxysporum f. sp. momordicae FomYjeF (Wei et al., 2023 ), F. oxysporum f. sp. radicis‐lycopersici ForMC69 (Sasaki et al., 2022 ), FoFGA1 (Jain et al., 2002 ), FoCPKA (Kim et al., 2011 ) and F. oxysporum f. sp.…”
Section: Identification and Pathogenicity Of Root Rot Pathogens In ...mentioning
confidence: 99%
“…The FomYjeF gene of F. oxysporum f. sp. momordicae not only regulates the production of spores but also inhibits the accumulation of host ROS (Wei et al., 2023 ). Wang, Zhao, et al.…”
Section: Identification and Pathogenicity Of Root Rot Pathogens In ...mentioning
confidence: 99%
“…ROS accumulation negatively regulates the pathogenicity of Fusarium oxysporum f. sp. momordicae [95]. Research data show that QSOX1 in plants is a REDOX sensor that restricts the production of ROS by connecting ROS and active nitrogen signals, and negatively regulates plant immunity [96].…”
Section: Effect Of Endogenous Hormones and Ros On The Neofunctionaliz...mentioning
confidence: 99%